Ідентифікація та моніторинг сільськогосподарських земель, що не обробляються внаслідок бойових дій - Дорош, Андрій Йосипович; Салюта, Вікторія Андріївна (НУБіП України, 2023)
This research utilizes remote sensing and GIS to assess the impact of military operations on land use, especially agricultural areas. Employing the NDVI index, we aim to identify non-cultivated agricultural land affected by hostilities. By analysing Sentinel-2 satellite images from March 20 to September 1, 2023, we construct an NDVI profile for wild grass and shrub vegetation. This profile, distinct from winter and spring crop profiles, helps identify lands left uncultivated due to conflicts. The study employs artificial intelligence tools to monitor and evaluate the state of affected lands, focusing on the environmental and human implications of military activities.
Keywords: ідентифікація сільськогосподарських земель; моніторинг сільськогосподарських земель; monitoring of agricultural land; Überwachung der landwirtschaftlichen Flächen; Identifizierung von landwirtschaftlichen Flächen; identification of agricultural land